Modeling of intercity passenger transportation system - Dolya, Constantine (Technology audit and production reserves, 2017)
The modern state of modeling of intercity passenger transportation systems is considered. It is determined that the search for various options for technologies of interaction between the society and the transport industry is constantly at the stage of searching for the best possible methods of transportation organization. To assess the proposed scientific approaches, full-scale measurements are carried out on the route flows of passengers on sections of route routes. The approach to modeling intercity passenger route transportation systems is considered as original in the article, taking into account economic, social and organizational components. These components determine the overall efficiency of the transport process. Together with this, the above approach can be improved. To do this, it is desirable to consider in more detail individual subsystems by mode of transport and separately allocate night and day transportation. Practitioners note that with the same parameters of the trip, people feel differently the consequences of a day and night trip. This can lead to different requirements for the transport network as a whole. But the above algorithm allows to take this into account. The means for assessing the performance parameters of the system of routes for passenger transportation systems are explored. The sequence of formation of the transportation system of intercity passenger transport is proposed, which relies on the achievements of science and practice and takes into account the patterns of distribution of transport correspondence between cities from the transport network. The attraction functions between cities are complemented in accordance with the number of inhabitants and purchasing power. New information has been obtained on the modeling of transport route systems for transportation of passengers between cities within the investigated system. This is more advantageous in comparison with analogues due to the consideration of ensuring the social and economic characteristics of the population, the possibility of increasing productivity by optimizing the use of the route network and meeting the economic interests of the transport industry. This is more advantageous in comparison with the analogues due to ensuring the registration of social and economic characteristics of the population of Ukraine, a possible increase in productivity by optimizing the use of the route network, satisfaction of economic interests of the transport industry.